235k views
1 vote
Help how do i solve this for the inverse

f(x) = (x - 2)/(3)

2 Answers

5 votes

Answer:


\boxed{f^(-1)(x)=3x+2}

Explanation:


f(x)=(x-2)/(3)\to y=(x-2)/(3)\\\\\text{exchange x and y}\\\\x=(y-2)/(3)\\\\\text{solve for y}\\\\(y-2)/(3)=x\qquad\text{multiply both sides by 3}\\\\y-2=3x\qquad\text{add 2 to both sides}\\\\y=3x+2

User JHK
by
5.1k points
5 votes

Answer:

The inverse function is 3x+2

Explanation:

To get the inverse function exchange x and y and then solve for y

y = (x-2)/3

Exchange x and y

x = (y-2)/3

Solve for y

Multiply by 3

3x = 3/3 *(y-2)

3x = y-2

Add 2 to each side

3x+2 = y-2+2

3x+2 =y

The inverse function is 3x+2

User DonutGaz
by
4.7k points